Patient Centered Perspectives On Diabetes – A Knowledge, Attitude And Practice (KAP) Study Among Indian Patients With Type 2 Diabetes Mellitus (International Journal of Environmental Sciences, 2025)
Background: The effective management of diabetes is in the hands of the patient which in turn related to their knowledge, attitude toward diabetes and medication adherence. This is related to impact produced by public health interventions and education programmes.Objectives: The objective of the study was to assess the knowledge, attitude, and practice towards diabetes among the type 2 diabetes mellitus patients through questionnaire.Materials and Methods: This was a prospective, observational, cross-sectional study conducted in a Tertiary Care Hospital at Puducherry over a period of 6 month from March 2024 to August 2024. A Medical Compliance Questionnaire (MCQ) which was modified to suit the local situation was designed to inquire about the knowledge, attitude and practice of diabetes. Results: Total 153 patients of type 2 diabetes mellitus, in which 43 males and 110 females. The majority of participants (64.7%) had duration of illness ranging from 0-5years. Hypertension is the comorbidity frequently associated which constitutes to 52.9% (81 individuals). Overall study population had moderate knowledge about diabetes with mean knowledge score of 58.5%, moderate positive attitude towards diabetes with mean attitude score of 56.3%, and poor practices towards medication adherence with practice score of 46.6%.Conclusion: The knowledge and attitude towards the diabetes among the study population is quite satisfactory. But regarding the practice towards diabetes particularly on compliance and medication adherence is poor. Overall, improving diabetes related practices requires not only educating and motivating individuals but also building a supportive health care system which makes healthy behaviours easier to adopt and maintain.